The prognostic value of highly sensitive cardiac troponin assays for adverse events in men and women with stable heart failure and a preserved vs. reduced ejection fraction. (28th August 2017) - Gohar, Aisha; Chong, Jenny P.C.; Liew, Oi Wah; den Ruijter, Hester; de Kleijn, Dominique P.V.; Sim, David; Yeo, Daniel P.S.; Ong, Hean Yee; Jaufeerally, Fazlur; Leong, Gerard K.T.; Ling, Lieng H.; Lam, Carolyn S.P.; et al.
Abstract : Aims: Circulating biomarkers are important in the diagnosis, risk stratification and management of patients with heart failure (HF). Given the current lack of biomarkers in HF with preserved ejection fraction (HFpEF), we aimed to investigate the prognostic performance of the newly developed high‐sensitivity (hs) assays for cardiac troponin I (hsTnI) compared with troponin T (hsTnT) for adverse events in HFpEF vs. HF with reduced ejection fraction (HFrEF). Findings in these two HF subgroups were also compared with those in the recently defined HF with mid‐range ejection fraction (HFmrEF) subgroup. Methods and results: Both hsTnI and hsTnT were measured in 1096 patients with HFrEF [left ventricular ejection fraction (LVEF) <50%; n = 853] or HFpEF (LVEF ≥50%; n = 243) enrolled in the Singapore Heart Failure Outcomes and Phenotypes (SHOP) study. Both troponin assays were more strongly associated with the composite endpoint (all‐cause mortality or first rehospitalization for HF) in HFpEF than in HFrEF. The hsTnT assay provided the greatest additional prognostic value in HFpEF in comparison with hsTnI and NT‐proBNP. TnI was more strongly associated with composite events in men with HFpEF [hazard ratio (HR) 3.33, 95% confidence interval (CI) 1.82–6.09; P < 0.001 per standard deviation (SD) increase in log‐transformed hsTnI] than in women with HFpEF (HR 1.35, 95% CI 0.94–1.93; P = 0.10 per SD increase in log‐transformed hsTnI). Conclusions: There is a potential role for the prognostic use of high‐sensitivity troponin assays, particularly hsTnT, in men and women with HFpEF. The predictive association of hsTnI with outcome appears strongest in men with HFpEF.